Negociação de regras sobre Barreiras Técnicas ao Comércio nos Acordos Preferenciais de Comércio: ponderações para o Brasil em negociações com África do Sul, China, Estados Unidos da América, Índia, Rússia e União Europeia - Carvalho, Marina Amaral Egydio de (2014)
preferential trade agreements negotiated by South Africa, Brazil/Mercosur, China, U.S.A, India, Russia and the European Union. Such an analysis is relevant mostly because, after the creation of the WTO and of the Agreement on Technical Barriers to Trade (TBT), several preferential trade agreements were negotiated, thus, extending or creating new rules on technical barriers its signatory countries. This study suggests some conclusions on how Brazil could negotiate this subject in future preferential trade agreements. Additionally, it suggests patterns and standards that may followed in future negotiations with the abovementioned countries. One of the scope of the work was to analyze how preferential trade agreements are related to the TBT Agreement, which are the similarities between the group of agreements analyzed, which were the new topics regulated in the trade agreements when compared to the WTO, which are the preferred policies of the subject countries and how Brazil could take advantage of this empirical analysis in future negotiations. The main purpose of this work is to encourage Brazil to develop a trade policy for negotiation of this specific topic, which may be actually followed and that, unless this is the actual trade objective of the negotiation, is not translated as a mere repetition of rules already in place